Panic Disorder Versus Thyroid Medication Overuse: A Case Report - Rosmina, Putri; Samuel Timothy (HM Publisher, 2024)
Introduction: Panic disorder is defined as the occurrence of spontaneous panic attacks that are not triggered by any specific stimulus. The symptoms of panic disorder include panic episodes that occur frequently and unexpectedly, as well as anxiety about the possibility of experiencing further panic attacks, the repercussions of panic attacks, or a change in behavior as a result of panic attacks. This study presented the diagnosis and treatment of panic disorder comorbid with thyroid medication overuse. Case presentation: A 36-year-old female patient presented to the emergency room with a primary concern and symptoms consistent with panic disorder, including experiencing a sense of losing control or impending death, chest pain, difficulty breathing, rapid heartbeat, excessive perspiration, trembling, and dizziness. The patient experienced significant periods of anxiety between episodes, preoccupied with the anticipation of the next occurrence. Each episode had a duration of roughly 15 minutes. The patient refutes any history of alcohol or drug misuse, and her sole medical condition is hypothyroidism. Subsequently, we perform a comprehensive analysis of the thyroid profile and make a referral to an internal medicine specialist for collaborative treatment. We treated the patient with a combination of a selective serotonin reuptake inhibitor (SSRI) fluoxetine 20 mg/day and a course of cognitive-behavioral therapy. Conclusion: Repeated episodes of intense panic attacks, accompanied by feelings of anxiety and observable alterations in behavior, distinguish panic disorder as a medical illness. The treatment involves the use of selective serotonin reuptake inhibitors, antidepressants, and cognitive behavioral therapy.